Revisiting the Spleen—An Imaging Review of the Common and Uncommon Splenic Pathology - Nadeem, Meshaal; Tiwari, Hina Arif; Jambhekar, Kedar; Shah, Hemendra; Ram, Roopa (Journal of Gastrointestinal and Abdominal Radiology, 2021)
The spleen is the largest lymphatic organ and is responsible for both hematological and immunological functions. Several common etiologies such as trauma, developmental variants, infectious/inflammatory conditions, and benign and malignant lesions can occur in the spleen. The role of imaging modalities such as ultrasound (US), computed tomography (CT), and magnetic resonance imaging (MRI) in diagnosing these conditions continues to evolve. The main objective of this review article is to illustrate the role of imaging in identifying the common and uncommon pathology of the spleen.
Keywords: sclerosing angiomatous nodular transformation; spleen; spontaneous rupture; hydatid; sarcoidosis; lymphoma